Biodiversity and endemism of the western Amazonia land snails Megalobulimus and Systrophia - Ramírez, Rina (2012)
In this work we performed a biogeographic study of two genera of Amazonian land snails, Megalobulimus (Strophocheilidae) and Systrophia (Scolodontidae). We used samples from different regions of the Peruvian Amazon, as well as bibliographic information. We analyzed both nuclear (5.8S-ITS2-28S rRNA) and mitochondrial (16S rRNA) genes to reconstruct phylogenies and obtain hypotheses concerning the evolutionary relationships among Amazonian genera and other species with global distribution. The nuclear phylogeny allowed us to determine the evolutionary position of both genera, and the mitochondrial phylogeny permitted the differentiation of species at the intrageneric level. We found that Megalobulimus clustered with the non-achatinoid clade within Stylommatophora, as expected, but its relationship to family Acavidae could not be demonstrated. Systrophia did not cluster with any of the two established clades, but formed a basal one within Stylommatophora. The mitochondrial gene 16S rRNA allowed us to differentiate Megalobulimus species, and performed well for DNA barcoding of these edible snails. Biogeographical analysis revealed several endemic species in the Peruvian Amazon within both genera, highlighting the Chanchamayo and Inambari biogeographic units.